2021
DOI: 10.1093/cvr/cvab161
|View full text |Cite
|
Sign up to set email alerts
|

Senescence mechanisms and targets in the heart

Abstract: Cellular senescence is a state of irreversible cell cycle arrest associated with ageing. Senescence of different cardiac cell types can direct the pathophysiology of cardiovascular diseases such as atherosclerosis, myocardial infarction, and cardiac fibrosis. While age-related telomere shortening represents a major cause of replicative senescence, the senescent state can also be induced by oxidative stress, metabolic dysfunction, and epigenetic regulation, among other stressors. It is critical that we understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 174 publications
0
86
0
Order By: Relevance
“…Some experimental studies have suggested that contractile function is also impaired with age [ 26 , 27 ]. Cardiac cycle duration is prolonged with an increase in both contraction and relaxation times.…”
Section: Aging Cardiac Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some experimental studies have suggested that contractile function is also impaired with age [ 26 , 27 ]. Cardiac cycle duration is prolonged with an increase in both contraction and relaxation times.…”
Section: Aging Cardiac Changesmentioning
confidence: 99%
“…Several genetic, molecular and biochemical abnormalities are involved in the structural and functional myocardial changes during aging [ 9 , 26 , 35 , 36 , 37 ]. These abnormalities are mainly characterized by changes in contractile proteins and cardiac excitation-contraction coupling, decreased contractile response to β-adrenergic stimulation, increased systemic and myocardial oxidative stress and renin–angiotensin activity, and metabolic changes [ 3 , 26 , 27 ].…”
Section: Aging Cardiac Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the P53/P21 pathway is primarily triggered by telomere dysfunction and DNA damage (Donato et al, 2018). P21, a cyclin-dependent kinase inhibitor, is responsible for the initial cell cycle arrest at G1/S or G2/M (Chen et al, 2021). In contrast to apoptosis, senescent cells are stably viable and have the potential to produce or release a wide range of inflammatory cytokines and chemokines, termed SASP .…”
Section: Discussionmentioning
confidence: 99%
“…Telomere lengths consist of TTAGGG repeats in tandem that are reduced by multiple conditions including cellular aging, cellular senescence and apoptosis, cancer processes, heart and lung conditions, Alzheimer's disease, etc. [193][194][195][196][197][198][199][200]. Shorter telomeres have been described in PBMCs of PM males compared to controls or FM carriers, regardless of FXTAS or dementia diagnosis [201][202][203].…”
Section: Telomere Shortening In Premutation Carriersmentioning
confidence: 99%